2015
DOI: 10.1177/0734242x15597998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemical analysis after steam pretreatment of lignocellulosic agricultural waste biomass from Williams Cavendish banana plant (TriploidMusaAAA group)

Abstract: The accessibility of fermentable substrates to enzymes is a limiting factor for the efficient bioconversion of agricultural wastes in the context of sustainable development. This paper presents the results of a biochemical analysis performed on six combined morphological parts of Williams Cavendish Lignocellulosic Biomass (WCLB) after steam cracking (SC) and steam explosion (SE) pretreatments. Solid (S) and liquid (L) fractions (Fs) obtained from SC pretreatment performed at 180°C (SLFSC180) and 210°C (SLFSC21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The fermentation from these bananas contributes to greenhouse gas emissions, volatile organic compounds and feasts for pathogens and mosquitoes (Awedem et al, 2016). Some of these residues are composed mainly of cellulose and lignin, which are difficult to reduce with the usual windrow composting (Chanakya and Sreesha, 2012;Kamdem et al, 2015).…”
Section: Banana Productionmentioning
confidence: 99%
“…The fermentation from these bananas contributes to greenhouse gas emissions, volatile organic compounds and feasts for pathogens and mosquitoes (Awedem et al, 2016). Some of these residues are composed mainly of cellulose and lignin, which are difficult to reduce with the usual windrow composting (Chanakya and Sreesha, 2012;Kamdem et al, 2015).…”
Section: Banana Productionmentioning
confidence: 99%
“…Although techniques for extraction of fibres and papers from pseudo‐stem are available, they have not been widely adopted by industries mainly due to their bulky nature leading to a high transport cost (Cardeiro et al ; Srivastava et al ). In recent years, researchers investigated the pretreatment, hydrolysis and ethanol production from banana pseudo‐stem (Reddy et al ; Santa‐Maria et al ; Gabhabe et al ; Ingale et al ; Kamdem et al ; Guerrero et al ). From previous studies, it can be concluded that banana pseudo‐stem and crop residues are potentially suitable for biofuel production with optimal amount of reducing sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper studied the three main lignocellulosic residues of banana (leaves, pseudostem and rachis) with liquid hot water (six conditions) and steam explosion (two conditions) pretreatments . The third study compared three different severity factors with steam cracking and steam explosion . Finally, another work analysed high catalysed sulfuric acid steam explosion pretreatment of plantain rachis .…”
Section: Introductionmentioning
confidence: 99%